(untitled) (Journal of Hama University, 2019)
The aim of the research is to identify the relationship between the strategies of emotional regulation and social harmony. Differences in strategies of emotional regulation and social compatibility are defined according to gender variables. The study was based on the analytical descriptive approach. The research sample consisted of (373) students in the second grade of the secondary school. It used the measure of emotional regulation strategies and the measure of social compatibility. The study found the following results: The existence of a correlation between social compatibility and the strategies of emotional organization in the second grade students, and the absence of differences on the scale of strategies of emotional regulation according to sex variables, there are statistically significant differences between the average scores of the members of the research sample on the scale of social compatibility and for the benefit of males.